Regeneration pattern and genome-wide transcription profile of rhizome axillary buds after perennial rice harvest - Yao, Fan; Hu, Qingyi; Yu, Yingzhen; Yang, Lifan; Jiao, Shuliang; Huang, Guangfu; Zhang, Shilai; Hu, Fengyi; Huang, Liyu (Frontiers in Plant Science, 2022)
Perennial rice is a new type of rice, and its production technology can be harvested continuously for many years. This technology embodies a green and sustainable agricultural production mode that has obvious advantages in balancing agricultural ecology and food security. The difference in regeneration patterns between perennial and annual rice and the establishment of molecular regulatory pathways in dominant axillary buds after harvest in perennial rice are still unclear. In this study, perennial rice (PR23) and annual rice (Chugeng28) were used to investigate axillary bud growth patterns before and after apical spike removal. After elimination of apical dominance at different development stages, the axillary buds of rhizome nodes in perennial rice germinated fastest and then became novel seedlings. The axillary buds of the high-position nodes in annual rice grew faster than those of other nodes. Furthermore, the whole genome gene expression patterns of rhizome buds of compression nodes at 1, 3, 4, and 5 days after apical spike removal in perennial rice were analyzed by transcriptome. Compared with the control buds without apical removal, 264, 3,484, 2,095, and 3,398 genes were up-regulated and 674, 3,484, 1,594, and 1,824 genes were down-regulated at 1, 3, 4, and 5 days after apical spike removal, respectively. Trend analysis of the expressed genes at different time points was carried out, and a co-expression network was constructed to identify key genes during axillary bud growth. The results showed that 85 hub genes screened by 12 co-regulatory networks were mainly enriched in light system, photosynthesis-antenna protein, plant hormone signal transduction, ABC transporter and metabolic pathway, which revealed that photosynthetic signal and hormone signal played important roles in the regulation of axillary bud regeneration in perennial rice. Overall, this study clarified the difference in the regeneration pattern of axillary buds between perennial and annual rice and provided an overview of the complex regulatory networks during the regeneration of axillary buds in perennial rice.